Pengembangan Media Ular Tangga Berbasis Kontekstual Materi Melihat Karena Cahaya Mendengar Karena Bunyi Kelas V Sekolah Dasar - Eva Yolandha Fachrunnisya; Mimin Ninawati (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study focuses on the Development and feasibility testing of a contextual-based visual Snakes and Ladders learning media for teaching Integrated Science (IPAS), specifically the topics "Seeing Because of Light" and "Hearing Because of Sound" in Grade V of elementary school. The Snakes and Ladders media is designed to address students’ lack of understanding of the subject matter when delivered using conventional teaching methods. The research method employed is Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate). Validation results from media experts indicated a feasibility percentage of 97%, while validation by subject matter experts showed a percentage of 98%. The implementation of the media in a small group trial revealed that the Snakes and Ladders media is highly suitable for classroom use, with positive responses from students. This media is expected to enhance student creativity and motivation, as well as contribute to the Development of more engaging and effective learning resources.